A preliminary study in the alterations of mitochondrial respiration in patients with carbon monoxide poisoning measured in blood cells. (3rd July 2017) - Jang, David H.; Kelly, Matthew; Hardy, Kevin; Lambert, David S.; Shofer, Frances S.; Eckmann, David M.
Abstract: Objectives: Carbon monoxide (CO) is a colorless and odorless gas responsible for poisoning mortality and morbidity in the United States. At this time, there is no reliable method to predict the severity of poisoning or clinical prognosis following CO exposure. Whole blood cells, such as peripheral blood mononuclear cells (PBMCs) and platelets, have been explored for their potential use to act as sensitive biomarkers for mitochondrial dysfunction which may have a role in CO poisoning. Design: The objective of this study was to measure mitochondrial respiration using intact cells obtained from patients exposed to CO as a potential biomarker for mitochondrial inhibition with results that can be obtained in a time frame useful for guiding clinical care. This was a prospective, observational pilot study performed from July 2015 to July 2016 at a single academic tertiary care center that is the location of the region's only multi chamber hyperbaric. Measurements: Clinical characteristics, patient demographics, mitochondrial respiration and outcomes were recorded. Main results: There were 7 patients enrolled with a mean COHb level 26.8 ± 10 and with a mean lactate of 1.1 ± 0.4 mmol/L. All 7 CO exposures were related to heat generators used during winter months with two deaths. There was a positive correlation between maximal respiration and COHb levels with both high maximal respiration and high spare respiratory capacity correlating with a high COHb level. There was a subset of PBMCs ( n = 4) that were analyzed for Complex IV (cytochrome c oxidase) activity. Conclusions: In this pilot study, measurements can be performed in an appropriate timeline for clinical care with potential to serve as a prognostic marker. Further work is necessary to develop high-resolution respirometry as a clinical tool for assessing the severity of illness and guiding therapy.